2006
DOI: 10.1111/j.1349-7006.2006.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and glucose consumption in gastrointestinal adenocarcinomas: Correlation with markers of hypoxia, acidity and anaerobic glycolysis

Abstract: This study gives an insight into tumor metabolic activity by investigating oxygen and glucose content, together with their metabolic products carbon dioxide and acids-pH, in the arterial and venous blood of a tumor. Nineteen patients with gastrointestinal adenocarcinomas undergoing surgery were studied. Biochemical analysis showed that in a large subgroup of tumors, oxygen consumption was reduced while that of glucose was increased in malignant, as compared to normal tissues; these features were more evident i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 27 publications
2
36
0
1
Order By: Relevance
“…In addition, HIFs are believed to promote prolyl hydroxylase enzyme activity, which indirectly promotes collagen matrix synthesis. 44 However, the study suggested that the upregulation of HIF-1a alone is not sufficient to cause an overall significant increase in osteogenesis and metabolism in group 3 (low oxygen).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, HIFs are believed to promote prolyl hydroxylase enzyme activity, which indirectly promotes collagen matrix synthesis. 44 However, the study suggested that the upregulation of HIF-1a alone is not sufficient to cause an overall significant increase in osteogenesis and metabolism in group 3 (low oxygen).…”
Section: Discussionmentioning
confidence: 91%
“…6A), which elevates the level of glycolytic enzymes, collagen matrix synthesis enzymes, and angiogenic factors to enhance osteogenesis. [29][30][31]43,44 Due to the increased glycolytic rate, there is an increase in the rate of glucose consumption (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…The current consensus is that, in most tumors, pH i lies between 7.0 and 7.4, similar to non-tumor cells, whereas pH e is typically between 6.9 and 7.0 [14], although values as low as 6.0 have been reported [15]. Indeed, some in vivo tumors can acidify venous blood in patients [16] because of their low pH e (Fig. 1).…”
Section: The Ph Of Tumorsmentioning
confidence: 89%
“…Therefore, it is not correct to suggest that aerobic glycolysis is the exclusive ATP-generating system in cancer cells. In reality, in vivo tumors probably rely on both aerobic glycolysis and OXPHOS for their energy, the proportions of which are probably dependent on both the genetic background of the cancer cell (e.g., c-MYC oncogene expression and TP53 mutation), as well as its microenvironment [4], particularly intratumoral hypoxia, which induces hypoxia-inducible factor (HIF)-1α expression, an a priori transcription factor that in turn upregulates glycolytic enzyme gene expression [5].…”
Section: Overview Of Tumor Metabolismmentioning
confidence: 99%